Examination of bark content for different species of short rotation coppice - Szalay Dóra (IOP CONFERENCE SERIES: EARTH AND ENVIRONMENTAL SCIENCE, 2019)
Short rotation coppices (SRC) can produce large amount of dendromass in a short time. From an energetic point of view, one of the most important challenges are the outstanding amount of ash content, which is primarily generated due to the high bark content of the thin shoots. Our research was carried out for measuring bark content of four species/clones performed in three different vegetation years. The experimental plantation is located in the northwestern part of Hungary. The results show that the bark content strongly depends on the applied harvest frequency and tree species. Based on the measurements, the Robinia pseudoacacia and the Salix alba species have the largest bark content in the first year but the value can be reduced by around 50% by using longer harvest rotation. Having analyzed the whole stem, the bark percentage of the Populus x euramericana clones increased from 5.5% to 33.7% from the cutting height to the tip. The minimum value was at the diameter class of 24-28 mm. In the case of Robinia pseudoacacia the bark content ranges only between 3.0% and 20.0%. © 2019 Published under licence by IOP Publishing Ltd.